Pengaruh Fear of Missing Out terhadap Perilaku Phubbing Gen Z Pengguna TikTok di Kota Bandung - Lydia Affrillia Frans; Eni Nuraeni Nugrahawati (UNISBA Press, 2024)
Abstract. Phubbing is a term that refers to the act of ignoring people around you to focus on your smartphone. It stems from a continuous need to be connected and updated through social media on your smartphone, driven by the fear of missing out (FOMO). This constant need for social interaction can lead to phubbing behavior, as individuals become engrossed in seeking information and connecting with their friends in the digital world. Generation Z, the most prolific group of internet users in Indonesia, especially on TikTok, is the target of this research. The study aims to understand the impact of FOMO on phubbing behavior among Generation Z TikTok users in Bandung City. The sample size for this study comprises 384 participants, selected using non-probability sampling with convenience sampling techniques. The research uses a simple linear regression analysis with the help of SPSS for Windows to analyze the data. The data was collected using two adapted scales: the Fear of Missing Out scale from Przybyski et al. (2013) and the Phubbing scale from Chotpiyasunondh (2018). The research findings indicate a significant positive effect of the Fear of Missing Out on Phubbing behavior among Gen Z TikTok users in Bandung City. The effect is 0.619 or 69.1%, with the remaining 30.9% being influenced by other factors not included in the study. This means that as the Fear of Missing Out increases, so does the phubbing behavior of Gen Z TikTok users in Bandung City, and conversely, as the Fear of Missing Out decreases, so does the phubbing behavior. A cross-tabulation analysis revealed that female users were more likely to engage in phubbing, accounting for 31% of the total phubbing instances.Abstrak. Fenomena phubbing merupakan tingkah laku mengabaikan orang lain karena lebih memilih untuk fokus pada handphone. Suatu kebutuhan yang terus dicari dan harus dipenuhi melalui media sosial yang ada di smartphone yang memicu indikasi fear of missing out. Pemenuhan kebutuhan sosial ini yang menimbulkan perilaku phubbing, akibat individu mulai sibuk untuk mencari informasi dan ingin terhubung dengan teman-teman mereka di dunia maya. Generasi Z merupakan pengguna internet terbanyak di Indonesia, terutama pengguna TikTok. Tujuan penelitian ini untuk mengetahui pengaruh fear of missing out terhadap perilaku phubbing pada Generasi Z pengguna TikTok di Kota Bandung. Sampel penelitian berjumlah 384 orang, pengambilan sampel dengan teknik non-probability sampling dengan convenience sampling. Uji hipotesis menggunakan analisis regresi linier sederhana dengan bantuan SPSS for windows. Pengumpulan data menggunakan adaptasi skala fear of missing out dari Przybyski et al., (2013) dan phubbing scale dari Chotpiyasunondh (2018). Hasil penelitian menunjukkan bahwa terdapat pengaruh positif signifikan fear of missing out terhadap perilaku phubbing Gen Z pengguna TikTok di Kota Bandung sebesar 0,619 atau 69.1% dan sisanya 30.9% dipengaruhi oleh faktor lain yang tidak termasuk dalam penelitian ini. Hal ini berarti semakin tinggi fear of missing out maka semakin tinggi perilaku phubbing Gen Z pengguna TikTok di Kota Bandung, begitupun sebaliknya semakin rendah fear of missing out (FoMO) maka semakin rendah pula perilaku phubbing Gen Z pengguna TikTok di Kota Bandung. Hasil crosstab menunjukkan jenis kelamin perempuan lebih banyak melakukan phubbing sebanyak 31%.